2021
DOI: 10.3389/fonc.2021.758036
|View full text |Cite
|
Sign up to set email alerts
|

The Value of MRI Findings Combined With Texture Analysis in the Differential Diagnosis of Primary Ovarian Granulosa Cell Tumors and Ovarian Thecoma–Fibrothecoma

Abstract: ObjectiveThis study aims to explore the value of magnetic resonance imaging (MRI) and texture analysis (TA) in the differential diagnosis of ovarian granulosa cell tumors (OGCTs) and thecoma-fibrothecoma (OTCA–FTCA).MethodsThe preoperative MRI data of 32 patients with OTCA–FTCA and 14 patients with OGCTs, confirmed by pathological examination between June 2013 and August 2020, were retrospectively analyzed. The texture data of three-dimensional MRI scans based on T2-weighted imaging and clinical and convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…The present results revealed that the diagnostic performance of the MRI-based and combination models was similar, and no additional benefit was obtained in TA. These results were contradictory to recent findings reported by Li et al showing that TA-based and combination models were superior to the MBF-based model [ 22 ]. However, there were important differences between that study and the present study; (1) The number of parameters they initially applied in TA was 1,316, which was too big for the small sample size of their study (46 cases).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present results revealed that the diagnostic performance of the MRI-based and combination models was similar, and no additional benefit was obtained in TA. These results were contradictory to recent findings reported by Li et al showing that TA-based and combination models were superior to the MBF-based model [ 22 ]. However, there were important differences between that study and the present study; (1) The number of parameters they initially applied in TA was 1,316, which was too big for the small sample size of their study (46 cases).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it is time-consuming to delineate all slices. However, in a recent study, good findings were obtained for TA-based models using all slice data [ 22 ]; therefore, further studies are needed. The further development of our models will be achieved by addressing these issues in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have also stated that inverse-variance is correlated with the survival time of glioblastoma patients ( 35 ). In another study, Li has reported SAHGLE as an independent feature to differentiate between primary ovarian granulosa cell tumor and ovarian thecoma-fibrothecoma (OR = 1.034) ( 36 ). Weng et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that machine learning-model had potential in improving accuracy of early diagnosis and reducing clinical workload. However, researches on highgrade gliomas were limited and most previous studies focused on distinguishing between two types of tumors (47)(48)(49)(50). For this reason, we employed radiomics-based machine learning technology to distinguish among GAM, AA and AO, and this multi-classification study was more suitable for clinical requirements.…”
Section: Discussionmentioning
confidence: 99%